Project Based Learning Module Development On Design Curling Competency In SMK - Titi Pratitis; Jalius Jama (EDUTEC : Journal of Education And Technology, 2020)
Creativity activities and time in the process of learning curling hair design is not balanced with the achievement of learning so it is necessary learning media in the form of modules. The purpose of this research is to produce a print module based on Project Based Learning that can help students learn independently in an effort to improve the creativity of learning outcomes and practices. The research method used is Research and Development (R&D) with Four-D development model. Research subjects of students in grade XI Beauty System Smk Swasta PAB 12 school year 2020/2021. The results of the development research obtained are: (1) Project Based Learning-based modules, (2) The validity of Project Based Learning-based modules is declared valid with a value of 0.84 > 0.67, (3) Project Based Learning-based module practicality based on two lecturer responses is declared very practical with an average score of 88 and based on 18 student responses expressed very practical with an average score of 84, (4) Project Based Learning-based modules are declared effective, can improve aspects of student knowledge viewed from the resulting practice results. Based on the results of this research, it can be concluded that project based learning modules are valid, practical and effective as a learning resource on the competency of curling hair design.